Scientific Analysis of Apollo images - Amathes, Pyrrhon; Christodoulides, Paul (My University, 2016)
Since the mid-1970s there have been claims that elements of the Apollo program and its associated Moon landings were staged by NASA. A growing number of people maintain that the lunar landings were faked and that the Apollo astronauts did not actually walk on the Moon. In this paper we analyse some of the Apollo lunar surface images through computer software and basic scientific reasoning in order to prove or disprove whether the EVA photographs were staged. We examine some of the most outstanding cases through the use of Photoshop® and Google Earth (Moon) applications. The resultant image analysis demonstrates that the Apollo photography was staged, manipulated and/or altered. Consequently, the Apollo lunar surface photographic record cannot be relied upon as evidence of humans walking on the Moon. Google Earth (Moon) simulations also indicate that in the case of Apollo 17, the mission was staged. The Apollo moonscapes used were inaccurate presentations of reality with incorrect elevations and serious lunar feature omissions. An Apollo 15 mission panorama as presented in Google Earth (Moon) leads to the same conclusion.
Keywords: Apollo program; NASA; Apollo astronauts